2019
DOI: 10.1093/icb/icz034
|View full text |Cite
|
Sign up to set email alerts
|

A Tissue Comparison of DNA Methylation of the Glucocorticoid Receptor Gene (Nr3c1) in European Starlings

Abstract: Negative feedback of the vertebrate stress response via the hypothalamic–pituitary–adrenal (HPA) axis is regulated by glucocorticoid receptors in the brain. Epigenetic modification of the glucocorticoid receptor gene (Nr3c1), including DNA methylation of the promoter region, can influence expression of these receptors, impacting behavior, physiology, and fitness. However, we still know little about the long-term effects of these modifications on fitness. To better understand these fitness effects, we must firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…While there were differences in DNA methylation patterns in the blood, associated with urbanization, there was little evidence that this reflected a coordinated organismal response to environmental cues: sites of differential methylation between the two habitats were (i) not over‐represented in regulatory regions, (ii) less likely to occur in association with expressed genes, and (iii) not over‐represented in specific biological pathways; however, as in liver, DNA methylation in blood was negatively related to gene expression when DMSs were located in TSS regions. Although other studies have found DNA methylation patterns in blood to reflect environmental and social factors (Jimeno et al., 2019; Lea et al., 2016), tissue‐specific patterns of DNA methylation have been shown in mammals (Christensen et al., 2009) and birds (Siller & Rubenstein, 2019), and it is therefore not expected that all tissues will respond in the same way to environmental cues.…”
Section: Discussionmentioning
confidence: 98%
“…While there were differences in DNA methylation patterns in the blood, associated with urbanization, there was little evidence that this reflected a coordinated organismal response to environmental cues: sites of differential methylation between the two habitats were (i) not over‐represented in regulatory regions, (ii) less likely to occur in association with expressed genes, and (iii) not over‐represented in specific biological pathways; however, as in liver, DNA methylation in blood was negatively related to gene expression when DMSs were located in TSS regions. Although other studies have found DNA methylation patterns in blood to reflect environmental and social factors (Jimeno et al., 2019; Lea et al., 2016), tissue‐specific patterns of DNA methylation have been shown in mammals (Christensen et al., 2009) and birds (Siller & Rubenstein, 2019), and it is therefore not expected that all tissues will respond in the same way to environmental cues.…”
Section: Discussionmentioning
confidence: 98%
“…The fact that we found a significant association between methylation levels in this region and gene expression suggests that this region or nearby ones play a role in gene expression regulation, but this remains to be confirmed. Secondly, DNA methylation may diverge with cell type and among tissues 43,58 . The use of tissues that allow non-lethal sampling enables the collection of longitudinal data and becomes especially relevant in long-term studies, but whether different tissues show comparable epigenetic changes in response to environmental challenges or experimental manipulations remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that epigenetic biomarkers in peripheral tissues (e.g. blood) may be used to test for long-term environmental effects on DNA methylation patterns 38–40 , also for the Nr3c1 gene 4,18,25,41,42 , which is further supported by the fact that methylation patterns in blood have often been shown to correlate with methylation patterns in other tissues such as the brain 15,26,27 , but see 43 .…”
Section: Methodsmentioning
confidence: 95%
“…4E and SI Appendix, Fig. S5) following established protocols (39,40). These clusters varied according to allele (Fig.…”
Section: Resultsmentioning
confidence: 98%